Análisis de prácticas pedagógicas en enseñanza religiosa escolar en cuarto, quinto y sexto grado de EGB en la Unidad Educativa Fiscomisional profesor Polivio Saquicela del cantón San Juan Bosco-Morona Santiago - Nugra Pachar, Marco Vinicio (2015)
This written work presents a critical analysis of academic and pedagogical practices in religious instruction in schools, fourth, fifth and sixth grade of EGB, Education Unit Fiscomisional "Prof. Polivio Saquicela "San Juan Bosco Canton. From the data collected is intended to highlight the successes and failures, from a pedagogical perspective, in the process of teaching and learning. The analysis focuses on the major components that make up the teaching practice, demonstrating the procedures and actions of the teacher in the following aspects: planning, class methodology, content, interaction in class, educational resources, activities household and evaluation. The reflection, from these data, identifies limitations that merit overcome and the successes they deserve strengthening to achieve influence religious education in comprehensive and holistic formation of students. To get the proposed results, the research is based on case study and support the ethnographic method, and the conceptual reflection of pedagogical practice in this subject.